Viktiga faktorer för skogsägare vid gallring - Grönesjö, Rasmus (2016)
The purpose of this study is to investigate what the forest owners think is important in the care measure thinning. What factors are the most important and which size of machine does the forest owner want´s when they let a sawmilling company perform the thinning. The idea of this study is to give the sawmill industry an indication to what they should do to cater for the forest owners requirement and how to build a long – term relationship. The majority of the forest owners wanted small machines in thinning combined with the management program free thinning. This study is done with cooperation with Derome Skog and is thereby defined to southwest Sweden.